2020
DOI: 10.3390/jcm9061917
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: The Potential Treatment of Pulmonary Fibrosis Associated with SARS-CoV-2 Infection

Abstract: In December 2019, a novel coronavirus, SARS-CoV-2, appeared, causing a wide range of symptoms, mainly respiratory infection. In March 2020, the World Health Organization (WHO) declared Coronavirus Disease 2019 (COVID-19) a pandemic, therefore the efforts of scientists around the world are focused on finding the right treatment and vaccine for the novel disease. COVID-19 has spread rapidly over several months, affecting patients across all age groups and geographic areas. The disease has a diverse course; patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
146
0
17

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 160 publications
(164 citation statements)
references
References 132 publications
1
146
0
17
Order By: Relevance
“…It is also an example of unprecedented cooperation of scientists from every country united to find a cure and vaccine against one single pathogen, but also searching for future solutions. Apart from finding efficacious treatments against COVID-19, it is necessary to accommodate the needs of patients suffering from the complications of COVID-19, including pulmonary fibrosis ( Lechowicz et al, 2020 ), central and peripheral neuropathies, delirium ( Kotfis et al, 2020a , b ), depression and many other complications. Further research towards in-depth understanding of the pathological mechanisms of SARS-CoV-2 in humans is necessary to develop novel therapeutic drugs for COVID-19.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…It is also an example of unprecedented cooperation of scientists from every country united to find a cure and vaccine against one single pathogen, but also searching for future solutions. Apart from finding efficacious treatments against COVID-19, it is necessary to accommodate the needs of patients suffering from the complications of COVID-19, including pulmonary fibrosis ( Lechowicz et al, 2020 ), central and peripheral neuropathies, delirium ( Kotfis et al, 2020a , b ), depression and many other complications. Further research towards in-depth understanding of the pathological mechanisms of SARS-CoV-2 in humans is necessary to develop novel therapeutic drugs for COVID-19.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…Based on current knowledge, Covid-19 infection causes mild to moderate symptoms in the majority of patients. However, these early data also suggest that even if symptoms are just 'mild to moderate' during the acute infection, fibrotic lung damage develops in some, potentially leading to long-term complications for a subset of patients (Spagnolo et al, 2020;Leask, 2020;Lechowicz et al, 2020;George et al, 2020). It is well known that over-activated MCs play a crucial role in the development of fibrotic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…This has led to several proposals for consideration of antifibrotic therapies to prevent or to treat COVID -19 pneumonia. (19)(20)(21) One CT study showed imaging features of interstitial fibrosis such as interstitial thickening, air bronchograms, irregular interface, coarse reticular pattern and parenchymal bands in 44% of patients discharged after treatment for COVID-19. (17) The aim of this report is to document the evolution of DAD to the fibrosing pattern in a series of minimally invasive autopsies in thirty individuals who died from COVID-19 in Wuhan, China.…”
Section: Introductionmentioning
confidence: 99%